2015
DOI: 10.1108/ijmhsc-12-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing health promotion among ethnocultural minority older adults (EMOA)

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(46 reference statements)
1
1
0
Order By: Relevance
“…Our findings are consistent with other research in this area: similarly to Wang et al’s (2019) review of older immigrants’ experiences with primary care, we too identified the importance of language and culture (Wang et al, 2019); we also echo the findings of Khan and Kobayashi (2015) in their analysis of health promotion uptake by older immigrants, who also emphasized the importance of system navigation and how diverse life experiences may influence when and how an FBOA accesses and experiences the health care system (Khan & Kobayashi, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with other research in this area: similarly to Wang et al’s (2019) review of older immigrants’ experiences with primary care, we too identified the importance of language and culture (Wang et al, 2019); we also echo the findings of Khan and Kobayashi (2015) in their analysis of health promotion uptake by older immigrants, who also emphasized the importance of system navigation and how diverse life experiences may influence when and how an FBOA accesses and experiences the health care system (Khan & Kobayashi, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, several immigrant-related health interventions have been initiated in Denmark (Eskildsen et al , 2012) as well as in other Western countries (Nierkens et al , 2013). The current interest, both policy-wise and scientific, in immigrant-related health improvement interventions in Denmark and other Western counties reflects the vulnerable and socially and economically disadvantaged situation of non-Western immigrant groups[1] (Bhopal, 2007; Gideon, 2011; Hjern, 2012; Khan and Kobayashi, 2015; Lorant and Dauvrin, 2012; Statistics Denmark, 2009; Stronks and Kunst, 2009), and their poor health outcomes compared with the general population (Correa-Velez et al , 2011; Helweg-Larsen et al , 2007; Masmas et al , 2010; Singhammer, 2008; Smith and Szuster, 2000; Tiong et al , 2006; Yun et al , 2012). Denmark is becoming increasingly multi-cultural.…”
Section: Introductionmentioning
confidence: 99%